Model Pengembangan Pasar Tradisional Menuju Pasar Sehat di Kota Semarang - Heru Sulistyo; Budhi Cahyono (Jurnal Ekonomi dan Bisnis, 2010)
Global fenomena has condition a business activities must be manage more proffesional andinvolve the stakeholders. The traditional market as a public service have many competitiveat the future, like mini market and modern market. This study was designed to investigatepossibility of traditional market management to be region company especially on market institutionin Semarang municipality. The concept based on to revitalization of traditional marketmanagement to be health market. The population on this study are the buyers, the sellers,the communities, the assosiation of seller, and market coordinators. All of markets in Semarangmunicipality as a object of study. The amount of markets are 47 units. The variables ofstudy are focus on organization and human resources management, stakeholders, law, andbenchmarking. The study use descriptive approach with quantitative and qualitative analysis.The result show that organization structure and human resources capability of market institutionin Semarang municipality is not relevan with current condition. The organizational cannotcreate and support the competitiveness in industrial markets. Capability of human resourcesin market institution is not relevant for answer the era competitiveness. The recommendationof the study focus on reorganization of market institution and increase capability of humanresources management to increase market institution competitiveness.Keywords : Organization and Management, Regulations, Benchmarking, Traditional Market